AB0182 Baseline Findings from A Patient-Centered, Treat-To-Target Approach in Rheumatoid Arthritis. (15th July 2016) - Ruderman, E.; Greene, G.; Beaumont, J.; Muftic, A.; Bacalao, E.; Mandelin, A.; Eisenstein, A.; Cella, D.
Abstract : Background: The Patient Reported Outcomes Measurement Information System (PROMIS) is an NIH initiative to develop patient-reported outcome measures for use across chronic conditions. PROMIS instruments assess outcomes relevant in Rheumatoid Arthritis (RA) including pain interference, physical function social function, fatigue, and depression. We aimed to learn whether the use of PROMIS instruments could inform the treat-to-target (T2T) approach to RA management, and to understand whether patient reports of disease impact correlate with objective clinical measures. Objectives: For this study, patients are treated for 1 year using a T2T approach. Using PROMIS item banks, we developed patient-centered targets in five domains: pain, fatigue, depression, physical function, and social function. We report on the baseline status of the full sample of patients enrolled in the study (n=119) stratified by disease activity (remission or low disease activity, CDAI ≤10 vs. moderate or high disease activity, CDAI >10). We also report on patient satisfaction with the individualized T2T approach, in addition to clinician feedback on the feasibility and usefulness of this approach. Methods: Patients with RA diagnosed by 2010 ACR/EULAR criteria were recruited from our academic clinical practice. At baseline data collection, standard RA assessments included joint counts, RAPID3, and CDAI scores. The research assessment battery included clinical questionnaires, PROMIS CAT's (computer adaptive tests), prioritization of PROMIS domains, and selection of five items that patients felt were most important within their most highly prioritized domain. Results: The baseline sample consists of 119 RA patients with a median age of 57 years (range: 21–77). The sample was 91% female, 71% White, and 12% Hispanic. Approximately 54% (n=57) exhibited moderate or high disease activity (CDAI m=13.4; SD=11.0). When selecting prioritization areas for treatment targets, 39% of patients selected physical function, followed by 37% of participants selecting pain, 16% fatigue, 5% depression, and 3% social function. Those with high active disease were more likely to select pain (44% vs. 22%). Compared to the U.S. general population reference values for PROMIS (m=50; SD=10), patients reported worse fatigue (m=56.4), pain interference (m=57.6), and physical function (m=42.3). Baseline scores on depression and social functioning were closer to average in the general U.S. population. Patient feedback about the study has been positive. An overwhelming majority of patients reported that they would be "somewhat" (33%) to "very likely" (56%) to participate in similar treatment programs. Response from health care providers has been positive as well, with limited reports of negative impacts of data collection on clinic flow. Conclusions: Most patients selected physical function, pain, and fatigue as the most important domains for their personal treatment goal setting. Consistent with these selections, patients' health ratings in these domains were worse compared to the general population. We will continue to explore correlations between PROMIS scores and standard disease activity measures, as well as clinician impressions of the impact of these data on their treatment decisions. Disclosure of Interest: None declared